Supporting sAFE and GradUAl ReDuctIon of loNG-term BenzodiaZepine Receptor Agonist uSe: development of the SAFEGUARDING-BZRAs toolkit using a co-design approach. (1st April 2022) - Lynch, T; Ryan, C; Bradley, C; Foster, D; Huff, C; Hutchinson, S; Lamberson, N; Lynch, L; Cadogan, C
Abstract: Introduction: Long-term benzodiazepine receptor agonist (BZRA) use (>3 months) persists worldwide and poses risks of harm. Effective interventions are needed to address this issue. Aim: To develop an intervention to support discontinuation of long-term benzodiazepine receptor agonist (BZRA) use. Methods: The intervention development process built on previous qualitative work that used the Theoretical Domains Framework (TDF) to explore perceived barriers and facilitators to discontinuing long-term BZRA use (1). A co-design approach was used whereby lay individuals and professionals worked as equals during the research process based on principles of authentic participation and collaboration (2). The co-design team included five 'experts by lived experience' with experience of long-term BZRA use who previously provided input on other related work as patient and public involvement representatives or responded to an expression of interest call on social media. Two online co-design team meetings were held. During the first meeting, a summary of previous findings was presented together with a long-list of behaviour change techniques (BCTs) generated using established mapping matrices in which BCTs were reliably allocated to the TDF. Each team member independently documented their decision as to whether each BCT should be included in a short-list for potential inclusion in the final intervention using online polling software. The a priori decision rule was that 70% of team members had to agree regarding the inclusion/exclusion of a BCT. All other BCTs were then discussed at a follow-up meeting. A finalised list of BCTs for inclusion in the intervention was agreed at the second meeting using a consensus-based approach involving the same decision rule. Potential ways in which BCTs could be operationalised were then discussed. Results: Thirty BCTs were discussed and six BCTs were excluded. For example, team members recommended avoiding 'Social comparison' as individual circumstances and experiences of discontinuation and associated withdrawal symptoms are unique and not directly comparable. Given the number of included BCTs, the co-design team recommended presenting them as a toolkit. The SAFEGUARDING-BZRAs (Supporting sAFE and GradUAl ReDuctIon of loNG-term BenzodiaZepine Receptor Agonist uSe) toolkit comprises 24 BCTs: 'Goal setting (behaviour)', 'Review behaviour goal(s)', 'Review outcome goal(s)', 'Feedback on behaviour', 'Self-monitoring of behaviour', 'Social support (practical)', 'Social support (emotional)', 'Information about health consequences', 'Monitoring of emotional consequences', 'Information about emotional consequences', 'Prompts/cues', 'Habit reversal', 'Graded tasks', 'Pros and cons', 'Comparative imagining of future outcomes', 'Social reward', 'Self-reward', 'Reduce negative emotions', 'Distraction', 'Adding objects to the environment', 'Body changes', 'Verbal persuasion about capability', 'Focus on past success' and 'Credible source'. The toolkit includes recommendations targeted at primary care-based clinicians for operationalising each BCT to support BZRA discontinuation. Conclusion: The SAFEGUARDING-BZRAs toolkit has been developed using a systematic, theory-based approach that addresses identified limitations of previous research (e.g. lack of detailed intervention description). In terms of limitations, it is possible that a different group of individuals may have developed a different type of intervention. To overcome this, a priori decision rules were used for decision making. Further research is needed to assess the toolkit's usability and acceptability by service users and clinicians. References: (1) Lynch et al. Health Expect. [in press] DOI: 10.1111/hex.13392. (2) O'Donnell et al. BMC Health Serv Res. 2019;19(1):797